ANALISIS YURIDIS TERHADAP UPAYA PENINGKATAN KINERJA PEMERINTAH DAERAH MELALUI EVALUASI PENYELENGGARAAN PEMERINTAHAN DAERAH - Fachruddin Razi (Jurnal LEX SPECIALIS, 2010)
As a public servant goverment especially distric goverment must show representation the will of center goverment, in this case quality of the hard work from district goverment must be evaluated, so it will reach the essence of a goverment as a public servant, but this is not an easy work because this evaluation must have abasic condition and it include many institutions, such like goverment institution or a non goverment institution but although it hard to realize doesnt mean it cannot be realize, it must be begin with a one focus evaluation and it increased to became two, three evaluation and more. Key Note : Evaluation of goverment as a public servant